2009
DOI: 10.15560/5.4.783
|View full text |Cite
|
Sign up to set email alerts
|

Reptilia, Leptotyphlopidae, Leptotyphlops salgueiroi Amaral, 1954: distribution extension and geographic variation

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…Although females exhibited more thoracolumbar vertebrae than males, no statistic sexual dimorphism was detected (F (1,20) 5 2.3, P 5 0.14). Previous studies (Passos et al, 2005(Passos et al, , 2006Costa et al, 2009) reported sexual dimorphism in the number of middorsal and caudal scales in Trilepida salgueiroi. Because there is a correlation in number of caudal vertebrae and scales in scolecophidians (usually as 1:1 scale/vertebra; see Gans and Taub, 1965;Alexander and Gans, 1966), one would expect that sexual dimorphism should also be reflected in the vertebrae in T. salgueiroi.…”
Section: Vertebrae and Ribsmentioning
confidence: 89%
See 2 more Smart Citations
“…Although females exhibited more thoracolumbar vertebrae than males, no statistic sexual dimorphism was detected (F (1,20) 5 2.3, P 5 0.14). Previous studies (Passos et al, 2005(Passos et al, , 2006Costa et al, 2009) reported sexual dimorphism in the number of middorsal and caudal scales in Trilepida salgueiroi. Because there is a correlation in number of caudal vertebrae and scales in scolecophidians (usually as 1:1 scale/vertebra; see Gans and Taub, 1965;Alexander and Gans, 1966), one would expect that sexual dimorphism should also be reflected in the vertebrae in T. salgueiroi.…”
Section: Vertebrae and Ribsmentioning
confidence: 89%
“…Anatomical terminology follows Romer (), List (), and Holman () [atlas and axis], List () [pelvic girdle], Holman () [trunk and tail vertebrae], Hardaway and Williams () and Persky et al () [costal cartilages], Langebartel () [hyoid elements], Rieppel () [parabasisphenoid complex], Wallach () [larynx and tracheal cartilages], Kley () [suspensorium], Rieppel et al () [skull], Curcio () and Rieppel et al () [skull foramina]. We follow Passos et al (), and Costa et al () in considering specimens up to 250 mm of total length to be juveniles. We tested assumptions of sexual dimorphism for number of vertebrae with the aid of the software Statistic 7.0 for Windows (Statsoft, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is overlap in morphological characters of T. koppesi and T. salgueiroi, but the latter species attain higher dorsal and ventral scales counts (Pinto & Fernandes 2012 (Pinto & Fernandes 2012). Differences in scale counts between the two specimens are due to sexual dimorphism known from T. salgueiroi (Costa et al 2009).…”
mentioning
confidence: 88%
“…Trilepida is composed of 14 species, seven occurring in the Brazilian territory, most of them endemic of that country (Passos et al 2005, 2006, Costa et al 2009, Pinto & Curcio 2011, Pinto & Fernandes 2012, Costa & Bérnils 2015. Trilepida jani Pinto & Fernandes 2012 is one of the newest described species in the genus and up to now is known only from a few localities in southern Espinhaço, a 1,000 km-long mountain range extending from the center of Minas Gerais to the north of Bahia states (Silva et al 2008).…”
mentioning
confidence: 99%